(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objective: Increasing antifungal resistance and biofilm formation among Candida species is an intimidating public health concern, especially at the hospital settings. In light of this, the current study was designed to assess the biofilm-forming ability of clinically isolated Candida albicans and determine their antifungal susceptibility against both the planktonic and sessile forms. Methods: A total of 58 Candida isolates from different clinical samples received at the Microbiology laboratory of KIST Medical College and Teaching Hospital, Lalitpur, Nepal in between April to October 2018 were included in the study. Isolation and identification of C. albicans was done following standard microbiological procedures that comprised of microscopic observations along with germ tube formation and biochemical tests. Besides qualitative investigation of biofilm by tube method, it was also investigated quantitatively by crystal violet staining method and metabolic activity of the biofilm was assayed by tetrazolium (XTT) salt reduction method. Antifungal susceptibility pattern against common antifungal drugs was determined as planktonic and sessile Minimum Inhibitory Concentrations (MICs) by broth micro-dilution method. Results: Out of 58 Candida recovered from the total samples, 21(36.2%) were identified as C. albicans. The vaginal swabs showed a higher prevalence (57.14%, 4/7) of C. albicans whereas none were recovered from the wound swabs. Qualitative study of biofilm formation showed that 4 (19.1%) Candida albicans were strong biofilm producers, 11 (52.3%) isolates were moderate and 6 (28.6%) produced weak or none biofilms, whereas a majority (85.7%) of the isolates gave biofilm positive test in microtiter plate assay. The metabolic activity of the biofilm revealed that the average absorbance following the metabolic reduction of tetrazolium salt was 0.577. Interestingly, both the methods used for assessing biofilm productions correlated well (r=0.569, p=0.007). Most of the isolates were susceptible to Fluconazole (80.9%) at MIC 0.12 μg/mL, Amphotericin B (76.19 %) at MIC 0.25 μg/mL and Clotrimazole (80.9%) at MIC 0.25 μg/mL. In addition, sessile forms of C. albicans was found to have 2 to 8 fold increases in MIC compared to the planktonic cells. Conclusion: High prevalence of C. albicans in vaginal swabs may implicate that the women are more prone to vaginosis. The sessile forms are more resistant to antifungal agents and proper administration of antifungal targeting the biofilms should be prioritized only with susceptibility result interpretations.